2003
DOI: 10.1046/j.1095-8649.2003.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of conspecific and heterospecific alarm signals by juvenile pumpkinseed under weak acidic conditions

Abstract: Under neutral (pH 7·0) conditions, juvenile pumpkinseed Lepomis gibbosus exhibited significant antipredator responses, of similar intensities, to the chemical alarm cues of conspecifics, an allopatric congener the green sunfish Lepomis cyanellus and the artificial alarm cue of a sympatric prey guild member (Cyprinidae, hypoxanthine‐3‐N‐oxide). Under weakly acidic conditions (pH 6·0), however, no increase in antipredator behaviour was seen in response to hypoxanthine‐3‐N‐oxide and a quantitatively weaker respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…A similar loss of chemical alarm cue function has been demonstrated in a non-ostariophysan species, pumpkinseed sunfish (Lepomis gibbosus; Leduc et al 2003). Juvenile sunfish were exposed to the skin extracts of conspecifics, green sunfish (Lepomis cyanellus), an allopatric congener, and H3NO under neutral (pH 7.5) and weakly acidic (pH 6.0) conditions.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…A similar loss of chemical alarm cue function has been demonstrated in a non-ostariophysan species, pumpkinseed sunfish (Lepomis gibbosus; Leduc et al 2003). Juvenile sunfish were exposed to the skin extracts of conspecifics, green sunfish (Lepomis cyanellus), an allopatric congener, and H3NO under neutral (pH 7.5) and weakly acidic (pH 6.0) conditions.…”
Section: Introductionmentioning
confidence: 90%
“…Under neutral conditions, pumpkinseed sunfish exhibited strong antipredator behaviour in response to all three experimental stimuli (compared to distilled water controls). However, the response to conspecific and congener skin extracts was significantly reduced and completely absent for H3NO under weakly acidic conditions (Leduc et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated that within taxonomically related groups, the response to heterospecific chemical alarm cues can be evolutionarily conserved (Brown et al 2001a, 2003, Mirza & Chivers 2001b, Mirza et al 2001, Leduc et al, 2003. The general trend, however, is that the intensity of behavioural response to heterospecific alarm cues decreases as the phylogenetic distance between donor and receiver species increases (Shutz 1956, Mirza & Chivers 2001b, Mirza et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to alarm cues can elicit adaptive predator avoidance behaviour, such as reduced activity levels and increased hiding or tighter group cohesion [43]. These behavioural responses to alarm cues have been observed in a range of freshwater fishes, including fathead minnows (Pimephales promelas), finescale dace (Phoxinus neogaeus), pumpkinseed (Lepomis gibbosus) and rainbow trout (Oncorhynchus mykiss) [20,37,44]. However, predator avoidance behaviour was diminished or absent when these alarm cues were presented in experimental treatments acidified using a minute amount of sulfuric acid (often a major contributor to freshwater acidification) [20,38,45].…”
Section: Ecological Effects Of Acidification On Olfaction (A) Freshwamentioning
confidence: 99%
“…Thus, under acidic condition, the alarm cues appear to undergo molecular changes and become either completely degraded (i.e. non-functional) and unrecognizable, or the concentration of its active component is reduced below a threshold necessary to trigger an adaptive alarm response [44].…”
Section: (A) Freshwater Ecosystemsmentioning
confidence: 99%